Depletion of mesospheric sodium during extended period of pulsating aurora. Issue 1 (24th January 2017) - Takahashi, T.; Hosokawa, K.; Nozawa, S.; Tsuda, T. T.; Ogawa, Y.; Tsutsumi, M.; Hiraki, Y.; Fujiwara, H.; Kawahara, T. D.; Saito, N.; Wada, S.; Kawabata, T.; et al.
Abstract: We quantitatively evaluated the Na density depletion due to charge transfer reactions between Na atoms and molecular ions produced by high‐energy electron precipitation during a pulsating aurora (PsA). An extended period of PsA was captured by an all‐sky camera at the European Incoherent Scatter (EISCAT) radar Tromsø site (69.6°N, 19.2°E) during a 2 h interval from 00:00 to 02:00 UT on 25 January 2012. During this period, using the EISCAT very high frequency (VHF) radar, we detected three intervals of intense ionization below 100 km that were probably caused by precipitation of high‐energy electrons during the PsA. In these intervals, the sodium lidar at Tromsø observed characteristic depletion of Na density at altitudes between 97 and 100 km. These Na density depletions lasted for 8 min and represented 5–8% of the background Na layer. To examine the cause of this depletion, we modeled the depletion rate based on charge transfer reactions with NO + and O 2 + while changing the R value which is defined as the ratio of NO + to O 2 + densities, from 1 to 10. The correlation coefficients between observed and modeled Na density depletion calculated with typical value R = 3 for time intervals T 1, T 2, and T 3 were 0.66, 0.80, and 0.67, respectively. The observed Na density depletion rates fall within the range of modeled depletion rate calculated with R from 1 to 10. This suggests that the charge transfer reactions triggered by the auroral impact ionization at low altitudes are the predominant process responsible for Na density depletion during PsA intervals. Key Points: Observational investigation for the Na density depletion due to high‐energy electron precipitation during a pulsating aurora The charge transfer reactions triggered by the auroral ionization is the predominant process responsible for the sodium density depletion Simultaneous observation of the sodium density and electron density by the sodium lidar and EISCAT VHF radar